Siglec-15 Promotes Tumor Progression in Osteosarcoma via DUSP1/MAPK Pathway - Fan, Meng-ke; Zhang, Guo-chuan; Chen, Wei; Qi, Li-li; Xie, Ming-fang; Zhang, Yue-yao; Wang, Ling; Zhang, Qi (Frontiers in Oncology, 2021)
Recurrence and metastasis are important features of osteosarcoma (OS) that cause its poor prognosis. Aberrant expression of Sialic acid-binding immunoglobulin-like lectin 15 (Siglec-15) has been reported in various kinds of cancers. However, the expression and function of Siglec-15 in OS remain unclear. In cultured OS cells (143B cells and MNNG/HOS cells) and their xenograft mouse models, we found that downregulation of Siglec-15 could inhibit the proliferation, migration and invasion of by inducing epithelial-mesenchymal transition (EMT) in vitro and in vivo. Conversely, Siglec-15 overexpression promoted the growth, migration and invasion of OS cells in a significant manner. Then, we screened a number of differentially expressed genes (DEGs) between Siglec-15-knockdown group and control group by RNA-Seq assay. Among these DEGs, we found that dual-specificity phosphatase 1 (DUSP1/MKP1) was significantly downregulated after Siglec-15 silencing. We investigated the DUSP1 functions in influencing OS cells’ biology, and found that the proliferation, migration and invasion of OS cells were promoted by overexpressing DUSP1 and crucially, the proliferation, migration and invasion of Siglec-15-knockdown OS cells were rescued by overexpressing DUSP1. Mechanically, we further showed that DUSP1-mediated inhibition of p38/MAPK and JNK/MAPK expression was attenuated when Siglec-15 expression was inhibited, suggesting that Siglec-15 promotes the malignant progression of OS cells by suppressing DUSP1-mediated suppression of the MAPK pathway. Moreover, we showed that both Siglec-15 and DUSP1 were highly expressed in human OS tissues by immunohistochemistry. High Siglec-15 expression was associated with OS lung metastasis, and high DUSP1 expression was associated with the high Enneking stage. Kaplan–Meier analysis indicated that high expression of Siglec-15 could predict poor prognosis of OS patients. Altogether, these results showed that Siglec-15 expression promoted OS development and progression by activating DUSP1 and might be a novel target in OS treatment.